2016
DOI: 10.4314/ahs.v16i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing concentration methods: parasitrap® versus Kato-Katz for studying the prevalence of Helminths in Bengo province, Angola

Abstract: Background: Helminth intestinal parasitoses are responsible for high levels of child mortality and morbidity. Hence, the capacity to diagnose these parasitoses and consequently ensure due treatment represents a factor of great importance. Objectives: The main objective of this study involves comparing two methods of concentration, parasitrap and Kato-Katz, for the diagnosis of intestinal parasitoses in faecal samples. Methods: Sample processing made recourse to two different concentration methods: the commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The study showed that 8.9% of the schoolchildren had S. stercoralis infection. This value is higher compared to the prevalence of S. stercoralis infection found in other countries such as 2.1% in Madagascar ( Hakami et al, 2019 ), 2.2% in Zanzibar ( Knopp et al, 2008a ), 5.8% in Ethiopia ( Legesse and Erko, 2004 ), 0.2% in Angola ( Mirante et al, 2016 ) and 2.7% in Thailand ( Sedionoto et al, 2019 ). However, our prevalence is comparable to the 9.7% prevalence reported in the Eastern Caribbean Sea ( Kurup and Hunjan, 2010 ) and the 10.8% prevalence in Zanzibar ( Knopp et al, 2008b ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The study showed that 8.9% of the schoolchildren had S. stercoralis infection. This value is higher compared to the prevalence of S. stercoralis infection found in other countries such as 2.1% in Madagascar ( Hakami et al, 2019 ), 2.2% in Zanzibar ( Knopp et al, 2008a ), 5.8% in Ethiopia ( Legesse and Erko, 2004 ), 0.2% in Angola ( Mirante et al, 2016 ) and 2.7% in Thailand ( Sedionoto et al, 2019 ). However, our prevalence is comparable to the 9.7% prevalence reported in the Eastern Caribbean Sea ( Kurup and Hunjan, 2010 ) and the 10.8% prevalence in Zanzibar ( Knopp et al, 2008b ).…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, Kato-Katz technique was found not suitable for S. stercoralis ( Machicado et al, 2012 ; Hailu et al, 2020 ; WHO, 2020 ); however, during the field estimation, some of S. stercoralis may be recovered by this technique. The prevalence of strongyloidiasis by Kato-Katz method among preschool and schoolchildren was reported at 4% in Ethiopia ( Amare et al, 2021 ), 2.1% in Madagascar ( Hakami et al, 2019 ), 2.2% in Zanzibar ( Knopp et al, 2008a ), 9.7% in the Eastern Caribbean Sea ( Kurup and Hunjan, 2010 ), 5.8% in Ethiopia ( Legesse and Erko, 2004 ), 0.2% in Angola ( Mirante et al, 2016 ) and 2.7% in Thailand ( Sedionoto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whole stool samples stored at 25°C for 1 day resulted in a 23% (p < 0.0001) and 13% (p < 0.0001) decrease in hookworm FEC, respectively. However, the previous reports have found that both debris particles and egg morphological changes can be misdiagnosed [15,18,19]. Therefore, false-positive Kato-Katz thick smears where several eggs were counted might mistakenly point to another source of error (e.g., writing errors on the entry forms or eggs confused with eggs from different species) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Whole stool samples stored at room temperature for one day resulted in a mean hookworm FEC decrease of 23% (p < 0.0001) versus a 13% reduction (p < 0.0001). However, these previous reports found that both debris particles and egg morphological changes can be misdiagnosed [16,19,20]. Therefore, the false-positive Kato-Katz thick smears where several eggs were counted might mistakenly point to another source of error (e.g.…”
Section: Discussionmentioning
confidence: 99%